Persepsi Wisatawan Terhadap Objek Daya Tarik Wisata Di Pantai Ketapang, Kabupaten Pesawaran, Provinsi Lampung - Ahmad Agung Prayitno; Gunardi Djoko Winarno; Rusita Rusita Rusita; Sugeng Prayitno Harianto (Universitas Bangka Belitung, 2021)
The perception of tourists towards a tourist attraction object is very important because it can offer some advices to managers for developing it. This study aims to see tourist’s perceptions of tourist attractions object, infrastructure, facilities and services on Ketapang Beach using the Closed Questionnaire Method. The results showed that Ketapang Beach had six tourist attractions, namely the beauty of sunrise / sunset, the clarity of clean water, the white sand that surrounds the beach, embossed sand, outbound, camping ground and souvenirs. The highest tourist’s perception score for tourist’s attraction object was outbound and camping ground categories, while the lowest value for tourist perception score was the available of souvenirs which was in the sufficient category. Tourist perceptions of facilities and services were higher right under the Infrastructure and ODTW. The development is needing especialy on fixing road access and adding roadblock and also expanding the parking area, adding more kind of tourist attraction object, and introducing Ketapang Beach to the local community.